PENGARUH PRAKTIK KERJA INDUSTRI DAN EFIKASI DIRI TERHADAP KESIAPAN KERJA SISWA KELAS XI SMK NEGERI 1 BANYUDONO 2017/2018 - -, Anitya Khadifa -; -, Mintasih Indriayu -; -, Sudarno - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purpose of this research are 1) to know the effect of the industrial work practice and self-efficacy simultaneously on readiness of the students of grade XI in SMKN 1 Banyudono to work; 2) to know the effect of the industrial work practice partially on readiness of the students of grade XI in SMK N 1 Banyudono to work; 3) to know the effect of the self-efficacy partially on readiness of the students of grade XI in SMK N 1 Banyudono to work. This research is a type of descriptive quantitative research with ex-post facto method. The population in this study is all students of SMK Negeri 1 Banyudono as many as 350 students consisting of classes XI. The sample in this study amounted to 78 students taken with proportional random sampling. Methods of collecting data in the form of questionnaires and documentation. Data analysis used is multiple linear regression analysis. The results of this study show (1) Fstatistic = 26,572 > Ftabel = 3,117  with significan is 0,000 < 0,05 so, the conclusion is that the independent variable (industrial working practices and self efficacy) will affect the readiness of the students of grade XI in SMK N 1 Banyudono (2) Industrial work pratices has a tcount = 5,589 > ttable = 1,995, Ho is rejected and Ha is accepted. Means that partially industrial work pratices variable  gave a good and significan impact on readiness of the students of grade XI in SMK N 1 Banyudono to work (3) Self efficacy has a tcount = 3,462 > ttable = 1,995, Ho is rejected and Ha is accepted. Means that partially self efficacy variable gave a good and significan impact on readiness of the students of grade XI in SMK N 1 Banyudono to work.